Business Planning : Serunding Warisan Enterprise / Norazura Mohd ...[et al.] - Mohd, Norazura; Muhamad Ali, Malyana; Al-Amir, Shariliana Anis; Mustafah, Nur Farah afiqah; Razali, Nurul fadilah (2009)
Serunding Warisan is a business that will be get the higher sale citizens and operated in the food sector. Our business is focusing such us beef,chiken and fish meat floss.As we know the meat floss very famous especially in malay society and meat floss come from the east. The business is located in the middle of Pekan Machang and it is a very strategic place because it is near to many public facilities such as bus station and Pasar Besar Machang and other public gathering. Our business will begin its operation on 1st august 2009.It,s because the hari raya will be arrived and we take that time to start our business. There are several factors why we select this business